The formability of aero-engine alloys - Alan F. Turner (1974)
The alloys used in aero-engine manufacture have widely differing properties and are subject to a multitude of forming operations. Unfortunately, there are many cases of failure occurring during forming, even though a specification restricts the maximum thinning strain. Recently, difficulties involved in the formability of mild steel have resulted in the use of forming limit diagrams (FLD) to explain these anomalies. In this work a similar technique was applied to aero engine alloys. The FLDs for six commonly used aero engine alloys were determined by measuring the maximum, principal strain increments on the surface of a sheet metal blank. The blank was deformed to failure by fluid forming, using various dies to give different stress ratios. The maximum, principal strain was then plotted against the strain perpendicular to it, resulting in the FLD for that material. Further tests were performed with solid punch tooling and these results showed how various friction conditions can give rise to different stress ratios. The instability strains were determined and were virtually coincident with the maximum load condition. This allowed Swift's treatment of instability strains to be applied, after determining the work hardening characteristics of the material from uniaxial, tensile tests. Unfortunately, the simple agreement was poor, but by fitting the Swift relationship incrementally, it was found that an approximately constant work hardening exponent and anisotropy parameters could be obtained. However, the 12% Cr–Mo steels showed a variation in the anisotropy parameters consistent with the stress ratio, although the work hardening exponent remained constant. This implies that a preferred orientation develops at small strains in these materials.